Once‐daily vs twice‐daily tacrolimus for de novo living kidney transplantation patients including ABO/HLA compatible and incompatible: A randomized trial. Issue 12 (8th November 2018) - Okumi, Masayoshi; Unagami, Kohei; Furusawa, Miyuki; Kakuta, Yoichi; IIzuka, Junpei; Takagi, Toshio; Shirakawa, Hiroki; Shimizu, Tomokazu; Omoto, Kazuya; Inui, Masashi; Ishida, Hideki; Tanabe, Kazunari
Abstract: Tacrolimus (TAC) is available as a twice‐daily capsule (TAC‐BID), once‐daily capsule (TAC‐QD), and once‐daily tablet. Recipients with ABO‐incompatible/anti‐human leukocyte antigen (HLA)‐incompatible transplantation were excluded in previous trials and have thus not been evaluated. We conducted a 5‐year trial to determine whether TAC‐QD is noninferior to TAC‐BID for transplant outcomes. Adults who underwent de novo living kidney transplantation were randomly assigned (62 TAC‐QD; 63 TAC‐BID). We did not exclude ABO‐/HLA‐ incompatible transplantation. TAC was initiated 7 days preoperatively (0.10 mg/kg/d). Mycophenolate mofetil, methylprednisolone, and basiliximab were administered. The primary endpoint was graft failure (non‐censored for death). We performed a noninferiority test. The noninferiority margin was 10% in risk difference. Five‐year graft failure rates were 6.5% and 9.5% for TAC‐QD and TAC‐BID, respectively (noninferiority, P = 0.009). The estimated glomerular filtration rates were similar between the groups (noninferiority, P < 0.001). TAC‐QD did not have point estimates of risk difference above the inferiority margin in any assessed endpoints. However, a tendency of interaction was observed between biopsy‐proven acute rejection and the follow‐up period. In a living kidney transplant population with 40% of patients with ABO/HLA incompatibility, the effect of TAC‐QD was not appreciably worse on various clinical transplant outcomes than that of TAC‐BID over 5 years.